1992
DOI: 10.1029/92je01634
|View full text |Cite
|
Sign up to set email alerts
|

Magellan observations of extended impact crater related features on the surface of Venus

Abstract: A total of 57 parabolic‐shaped and 9 approximately circular extended, impact crater related features have been found in Magellan synthetic aperture radar (SAR) and thermal emissivity data covering 92% of the surface of Venus. The parabolic features are, with seven exceptions, oriented E‐W with the apex to the east and the impact crater located just west of the apex. They were first identified in the surface emissivity data derived from Magellan radiometry measurements, but the great majority are only clearly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(159 citation statements)
references
References 23 publications
3
154
2
Order By: Relevance
“…Radar-dark parabolas, observed around about 50 craters, are believed to be relatively ®ne-grained ejecta from the craters with which they are associated. Being injected into the upper atmosphere, these small particles are transported to the west by the E±W zonal wind, thus forming parabolas with their apex to the east (Campbell et al, 1992). Radardark parabolas occupy a total of about 8% of Venus' surface, while the areal distribution of other components of this unit is signi®cantly smaller.…”
Section: Description Of Geologic Unitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Radar-dark parabolas, observed around about 50 craters, are believed to be relatively ®ne-grained ejecta from the craters with which they are associated. Being injected into the upper atmosphere, these small particles are transported to the west by the E±W zonal wind, thus forming parabolas with their apex to the east (Campbell et al, 1992). Radardark parabolas occupy a total of about 8% of Venus' surface, while the areal distribution of other components of this unit is signi®cantly smaller.…”
Section: Description Of Geologic Unitsmentioning
confidence: 99%
“…Radardark parabolas occupy a total of about 8% of Venus' surface, while the areal distribution of other components of this unit is signi®cantly smaller. The discoverers of the dark parabola craters found that these craters are among the youngest features of the Venusian surface (Campbell et al, 1992). A special Fig.…”
Section: Description Of Geologic Unitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, while crater-filling dust deposits can potentially change floor sizes by partially burying crater walls, these deposits should affect floor brightness long before they achieve sufficient thickness to alter the floor morphometry. If the parabolic ejecta units on Venus can darken surfaces with layer thicknesses of only -•10-100 cm Campbell et al, 1992], then even a few meters of eolian dust should be enough to darken the brightest crater floor. Since thin deposits should form much faster than deposits over 100 m thick, we would therefore expect significant changes in floor brightness to be largely independent of the observed floor enlargements if the eolian mechanism dominated floor darkening.…”
Section: Eolian Mantlingmentioning
confidence: 99%